Biochemistry - Mary K Campbell (Cengage Learning India Private Limited, 2006)
The strength of the text is that it is clear, concise, colorful and current! The Biochemical Connections are very good, the students like them a lot. I would describe this as the very best, if not the only, biochemistry textbook on the market for an introductory, non-majors biochemistry course.\\I\'m especially impressed by the Biochemical Connections, Special Interest boxes; these are excellent, and a good idea. These and the sections on Techniques and the Chapter Overviews are first-rate.\\I would describe the text as a colorful, easy-to-read introductory text on biochemistry that provides nice connections between biochemistry and the real world.\